Book Review of “Lying Down in the Ever-Falling Snow: Canadian Health Professionals’ Experience of Compassion Fatigue” - Hart, David S. (Canadian Journal of Counselling and Psychotherapy, 2013)
Lying Down in the Ever-Falling Snow presents the results of phenomenological research conducted by 7 leading health care providers representing the range of caring professions. The various published definitions of compassion and compassion fatigue are discussed. Selections from research interviews with 25 volunteer health care providers about their “felt experience” of compassion fatigue are interwoven with the authors’ interpretative insights within 1 of 4 themes: bodily, temporal, spatial, and relational. The experience of hope and hopelessness are discussed, as well as the roles they play in compassion fatigue onset and recovery. In the final chapters, the authors consider aspects of care for the suffering caregivers.